A Phloem-Feeding Insect Transfers Bacterial Endophytic Communities between Grapevine Plants - Lòpez-Fernàndez, Sebastiàn; Mazzoni, Valerio; Pedrazzoli, Federico; Pertot, Ilaria; Campisano, Andrea (Frontiers in Microbiology, 2017)
Bacterial endophytes colonize the inner tissues of host plants through the roots or through discontinuities on the plant surface, including wounds and stomata. Very little is known regarding a possible role of insects in acquiring and transmitting non- phytopathogenic microorganisms from plant to plant, especially those endophytes that are beneficial symbionts providing plant protection properties and homeostatic stability to the host. To understand the ecological role of insects in the transmission of endophytic bacteria, we used freshly hatched nymphs of the American sap-feeding leafhopper Scaphoideus titanus (vector) to transfer microorganisms across grapevine plants. After contact with the vector, sink plants were colonized by a complex endophytic community dominated by Proteobacteria, highly similar to that present in source plants. A similar bacterial community, but with a higher ratio of Firmicutes, was found on S. titanus. Insects feeding only on sink plants transferred an entirely different bacterial community dominated by Actinobacteria, where the opportunistic human pathogen Mycobacterium sp., played a major role. Despite the fact that insects dwelled mostly on plant stems, the bacterial communities in plant roots resembled more closely those inside and on insects, when compared to those of above-ground plant organs. We prove here for the first time the potential of insect vectors to transfer entire bacterial communities between plants. We also describe the role of plants and bacterial endophytes in establishing microbial communities in plant-feeding insects.